2020
DOI: 10.3390/ijms21176012
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptor (GPCR) Signaling in the Carotid Body: Roles in Hypoxia and Cardiovascular and Respiratory Disease

Abstract: The carotid body (CB) is an important organ located at the carotid bifurcation that constantly monitors the blood supplying the brain. During hypoxia, the CB immediately triggers an alarm in the form of nerve impulses sent to the brain. This activates protective reflexes including hyperventilation, tachycardia and vasoconstriction, to ensure blood and oxygen delivery to the brain and vital organs. However, in certain conditions, including obstructive sleep apnea, heart failure and essential/spontaneous hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 141 publications
(182 reference statements)
0
12
0
Order By: Relevance
“…ROS have also been implicated in CB hyperactivity previously, although the focus so far has been on those derived from angiotensin II and NADPH oxidase [ 51 , 52 , 53 , 54 , 55 , 56 ]. Interestingly, it has been observed that mitochondrial superoxide dismutase nitration and protein expression is elevated in the CB following 7 days of chronic intermittent hypoxia (CIH), suggestive of elevated mitoROS production [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS have also been implicated in CB hyperactivity previously, although the focus so far has been on those derived from angiotensin II and NADPH oxidase [ 51 , 52 , 53 , 54 , 55 , 56 ]. Interestingly, it has been observed that mitochondrial superoxide dismutase nitration and protein expression is elevated in the CB following 7 days of chronic intermittent hypoxia (CIH), suggestive of elevated mitoROS production [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carotid body has a complex regulatory network. A variety of neurotransmitters or neuromodulators act on the corresponding receptors in type I cells or CSN afferent fibers to produce excitatory or inhibitory effects and ultimately regulate the input of CB type I cells' oxygen-sensitive signals (Aldossary et al, 2020;Ortega-Sáenz and López-Barneo, 2020). Many of these receptors are G protein-coupled receptors located not only in CSN afferent fibers but also in type I cells and type II cells (Guidolin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…G protein signalling has a major role in establishing and modifying CB function [1]. Previous reports have implicated G protein pathways in CIH mediated CB hyperactivity and include 5-HT [53], angiotensin II [32,36], endothelin [51,63] and adenosine [67] signalling.…”
Section: β-Adrenoceptor Blockade Reduces Cb Chemosensitivitymentioning
confidence: 99%